INOVASI PRODUK DAN PENGARUHNYA TERHADAP KINERJA PEMASARAN UMKM KERAJINAN DI KALIMANTAN TIMUR STUDI KUALITATIF - Azhari, Fachmi; Zainurossalamia ZA, Saida (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research aims to deeply analyze how product innovation practices, encompassing design and functionality dimensions, affect the marketing performance of handicraft MSMEs in East Kalimantan. Increased global competition requires MSMEs to move beyond traditional business models. This qualitative research uses a multi-case study approach in Samarinda and Balikpapan. Data collection was conducted through in-depth interviews with 12 MSME owners successful in innovation, observation, and product artifact documentation analysis. The results indicate that innovation based on customer co-creation and the adoption of sustainable materials significantly enhances brand equity and export market reach. The main scientific finding is that open innovation acts as a crucial mediator between innovation intensity and non-financial marketing performance. The study concludes by emphasizing the importance of knowledge management and collaborative networks to sustain competitive advantage.